Metode Picture And Picture Sebagai Upaya Peningkatan Pemahaman Konsep Merawat Hewan di Kelas II SDN Kepanjenkidul Kota Blitar - Ida Nurul Laila (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Abstract. Elementary education or elementary school is the initial momentum for children to improve their abilities, from elementary school they get immunity to learning which then becomes a habit they do in the future. Thematic learning in class II on how to take care of animals, there are still many students who are not used to doing it at home. For this reason, there is a need for education from schools that foster students' love for animals and plants in the student's environment. This learning must be started early so that in the future students are accustomed to doing it at home. The thing that is currently blocking it is the existence of a pandemic so that learning from teachers must be online, but teachers must be more creative in developing their professionalism. The teacher uses the Picture and Picture learning method so that online learning goes well. Based on this, qualitative research is needed on students in learning about Caring for Animals. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions.